Creation of energy-efficient building envelope based on phase-change materials (PCM) - Benachir Nouhaila,; Taoufiq Mouhib,; Farida Bendriaa, (Eximia, 2022)
The building envelope (walls, floor, windows,roof) is a very important element of the design as it can have a effect on the energy performance of the building, that is comfortable all year round can be achieved with reasonable levels of insulation, reduced thermal bridging, summertime shading features, and ventilation.Most building materials have either a relatively low thermal mass or a high structural mass, such as concrete. or a high structural mass, like concrete. The provision of thermal inertia is therefore necessary but comes with disadvantages and restrictions in terms of structural design, aesthetics and ecology. However, there is a type of high thermal inertia and excellent specific properties, which is becoming more and more important in the design of new phase change materials (PCM).The high thermal inertia of these materials stems from their ability to change phase at a user-adjustable temperature. Indeed, the absorbed during the melting of the PCM is stored in the material and released at the desired time when the PCM solidifies by an exothermic process. Depending on the properties of the thermal zone where we are, it is therefore possible to integrate PCM and optimize their parameters in order to favorably dephase the energy consumption peaks and energy consumption and, by the same token, significantly reducing the use of the HC system. Consequently, the integration of this PCM in the envelopes of new buildings or in renovation would contribute to reduce the energy bill in the building sector in Morocco. So the (PCM) represents a sustainable alternative to reduce energy consumption for this a thermal dynamic simulation was realized with TRNSYS 204. Since PCM involves large latent heat at small temperature phase changes, PCM is used for temperature stabilization and for storing heat with large energy densities and capacity the storage in combination with rather small temperature changes. The simulation was carried out for the climate zone of Morocco (Casablanca Nouasseur). The results of the simulation showed that the use of phase change materials in brick walls reduced overheating in the summer period, decreasing the ambient temperature of the indoor air by 3 degree C.